Hybridation and selective destruction as propelling strategies in the historical centres of Salanamca and Stockholm (Ciudades, 2017)
The goal of this article is to address the question of the variability and flexibility in the historical centers, analyzing the activities of two case studies in Europe: Salamanca and Stockholm. Both of them are clear examples of good adaptability and evolution of the fabric in a contemporary context and the result of very different urban policies. Stockholm is more radical and visionary, working by "selective destruction”, removing the unnecessary and not adaptable to create a more livable city. Salamanca’s strategy is more conservative and runs by  "hybridization". It mixes the old and the new, conscious of the value of history and culture, and finds a way to give a new meaning. Both strategies involve the rejection of an obsolete "living museum" and therefore an approach to a better quality of their centers, using propelling tools, not pathological, which improve their urbanization process.
Keywords: propelling; hybridation; destruction; Salamanca; Stockholm